STATINS: A NEW THERAPEUTIC APPROACH FOR THE TREATMENT OF NEUROPATHIC PAIN - MELKANI, INDU; KUMAR, BIMLESH; PANDEY, NARENDRA KUMAR; BAGHEL, DILEEP SINGH; SINGH, SAURABH (International Journal of Applied Pharmaceutics, 2024)
Due to a lesion or chronic illness state that affects the somatosensory nerve system, Neuropathic Pain (NP) is a terrible ailment. NP has recently been a top problem for the pharmaceutical and medical industries. For the therapy of NP, stains may offer an additional source of illumination. By preventing 3-Hydroxy-3-Methylglutaryl-Coenzyme a (HMG-CoA), it prevents the rate-limiting step in cholesterol production. HMG-CoA reductase inhibitors, which have a pleiotropic impact in addition to the cholesterol-lowering effects of statins, have also been linked to neuropathic pain. According to reports, statins can worsen endothelial dysfunction by making more nitric oxide available. Antioxidant, antiproliferative, and immunomodulatory activities are known to exist in it. It primarily comes highly suggested for cardiovascular issues and helps to reduce inflammation. Atherosclerotic plaque is under its control. To the best of our knowledge, this subject has not yet been the subject of clinical research in humans. Up until now, most of the evidence pointing to a connection between statins and neuropathic pain has been speculative. As a result, this evaluation should be considered a synopsis of what is already known, what is being investigated, and where more research might be needed. This review assesses the statins for neuropathic pain in preclinical as well as clinical research.